"Fake News" on Sexual Minorities is "Old News": A Study of Digital Platforms as Spaces for Challenging Inaccurate Reporting on Ugandan Sexual Minorities. Issue 4 (2nd October 2019) - Strand, Cecilia; Svensson, Jakob
ABSTRACT: For sexual minorities in Africa, fake news is nothing new. However, with the arrival of self-controlled digital platforms, sexual minorities are presented with new ways to counter coverage that misrepresents the community. Inspired by affordance theory and agenda-setting theory, this study explores whether self-controlled digital platforms are used to challenge false media reports on sexual minorities in Uganda, and if so, to what extent. Through a cross-media research design, the largest English-language daily newspaper, the government-owned New Vision, is analysed and positioned against the main sexual minority network's (SMUG's) public Facebook and Twitter accounts at two points in time in 2013/2014 and in 2018. The study finds that, although social media channels afford direct engagement with false media reports, the platforms are under-utilised as spaces regarding countering false reporting on LGBTQIs. Furthermore, this lack of engagement with the media was found to be stable over time.